Mycotic Keratitis – Signs, Diagnosis, Therapy - Bock, Robert; Roth, Mathias; Geerling, Gerd (Klinische Monatsblätter für Augenheilkunde, 2025)
Mycotic keratitis is a rare but serious infection of the cornea that occurs particularly in wearers of contact lenses and in patients with systemic diseases, such as diabetes or immunosuppression. It is often caused by filamentous fungi such as Fusarium spp. and Aspergillus spp. or by yeasts, in particular Candida spp. The diagnosis of mycotic keratitis is challenging, as clinical signs are often non-specific. Diagnosis includes in vivo confocal microscopy, fungal cultures and histopathological examinations. Early and targeted diagnosis is crucial, in order to avoid serious complications. Treatment is based on the use of antimycotics such as natamycin and voriconazole. In refractory cases, early surgical intervention, usually by means of keratoplasty, is necessary. The aim of this article is to provide a comprehensive overview of the aetiology, diagnosis and treatment of mycotic keratitis and to provide clinical recommendations for the effective management of this challenging disease.
Keywords: keratomycosis; Candida spp.; Fusarium spp.; contact lens-associated keratitis; infectious keratitis